Effect of Mangiferin, a Naturally Occurring Glucosylxanthone, on Reproductive Function of Rats - Chattopadhyay S.; Chattopadhyay U.; Shukla S.P.; Ghosal S. (My University, 2025)
Female albino rats, treated with mangiferin at daily doses of 5 mg/100 g ip for 3 days during mid-gestation, showed complete fetal resorption. Administration of a mangiferin-Cu2+ (1:1) complex, along with mangiferin, attenuated the effect of mangiferin and restored the completion of gestation in 60% of the rats. The mother rats that completed gestation successfully did not show any post-natal abnormality, and the litters born were also normal. Mangiferin treatment of non-gestating female rats caused little or no changes in their organ weights. However, changes in the protein and protein-DNA ratios of several organs were statistically significant. Mangiferin also modified the ascorbic acid retention capacity of adrenal glands of male rats in vitro. These findings are appraised in view of mangiferin as a potential antifertility agent. © 1984, Plenum Publishing Corporation. All rights reserved.